A review of the Bank of Canada's market operations related to COVID-19 - Grahame Johnson (Bank of Canada, 2023)
The economic lockdowns that began in March 2020 in response to the COVID-19 pandemic led to an unparalleled level of financial market disruption. Investors sought liquidity by selling financial assets and drawing down loans and credit lines. The speed, scale and one-way nature of these transactions caused an almost complete breakdown of market functioning. In response, the Bank of Canada launched 10 extraordinary programs, 9 of which had never been used before, to restore market functioning. As market conditions improved, 9 of the 10 programs were wound down. One, the Government of Canada Bond Purchase Program, was continued and transitioned into a monetary policy tool. In general, most of the programs were well designed and effectively executed - an impressive achievement given the circumstances under which they were conceived, developed and deployed. The extreme level of uncertainty and the magnitude of the downside risks to economic and financial activity warranted an aggressive response. Going forward, however, several areas exist where program design and implementation could be changed if these programs ever need to be used again. Overall, the design and implementation recommendations for future interventions focus on the need to ensure the programs are appropriately structured, in terms of both size and duration, for the financial and economic circumstances. Given the speed with which the outlook can change, program parameters must be flexible, and the Bank must be nimble in making the necessary adjustments.
Keywords: D47; E41; E5; G01; G14; G21; G23; H12; 330; Coronavirus disease (COVID-19); Financial markets; Financial stability